Environmental Impact Assessment of Mining Activities in the Vicinity of Madenköy (Nigde) Using Biogeochemical Modeling - Gedik, Tulin; Akyildiz, Mustafa (Asian Journal of Chemistry, 2013)
Detection, distribution and assessment of environmental impacts of covered mine ores uses biogeochemical methods in addition to geochemical methods. This study analyzed environmental effects of mineralization and mining activities on plants, using biogeochemical methods. The study also determined spatial distribution of biogeochemical parameters by modeling through geochemical and geostatistical methods. The study used Astragalus sp., Berberis vulgaris, Colutea cilicia, Juniperus oxycedrus, Paliurus spina-christi, Pinus nigra, Rosa canina plant species, which are abundant and widely distributed in the region. It was found that among plant species, branch of Juniperus oxycedrus were found to be indicators for Pb (r = 0.7541; p = < 0.01; n = 15) and branch of Pinus nigra were found to be indicators for Zn (r = 0.79; p = < 0.01; n = 13). Analyses showed that metal accumulation varied in each plant. It was observed that biologic absorption coefficients corresponded to strong absorption (BAC = 1-10) values in Zn and Pb elements.